THE FREE VERSE AS A HYPEROBJECT: (Spasovska, Suzana V. The freedom of the verse, Study of the Macedonian freeverse, Skopje, 2021, 272 pp.) (Journal of Contemporary Philology, 2022)
(Spasovska, Suzana V. The freedom of the verse, Study of the Macedonian freeverse, Skopje, 2021, 272 pp.)
Keywords: Review